Cognitive Behavioral Therapy for Mental Health and Stigma Among PLWH in Low and Middle-Income Countries: A Systematic Review - Hasanudin Hasanudin; Sri Winarni; Elizabeth Risha Murlina Lema; Achmad Tirmidzi; Sunari Sunari (Dewan Pimpinan Daerah Persatuan Perawat Nasional Indonesia Kota Blitar, 2026)
burden of mental health disorders and HIV-related stigma, which critically hinders adherence to antiretroviral therapy (ART). Cognitive Behavioral Therapy (CBT) has emerged as a promising evidence-based psychological intervention. However, its effectiveness across diverse populations and delivery formats in LMICs has not been adequately synthesized. This systematic review aimed to evaluate the effectiveness of CBT on mental health and stigma reduction among PLWH in LMICs. A systematic review was conducted in accordance with the PRISMA guidelines for RCT articles published in Scopus, Science Direct, and PubMed databases between January 1, 2021, to April 9, 2026. The keywords used were “Cognitive Behavioral Therapy” AND “Mental Health OR Stigma” AND “People Living with HIV” OR “Randomized Controlled Trial.” Risk of bias was assessed using the Cochrane Risk of Bias Tool version 2 (RoB 2). Seven RCTs involving 1.786 participants from six LMICs in Africa and one in South Asia were included. All studies consistently reported clinically significant reductions in depressive symptoms and internalized stigma following CBT interventions, regardless of group, individual, or self-administered delivery format, and regardless of whether the intervention was delivered by a mental health specialist or a trained non-specialist. The risk of bias assessment indicated that one study had a low risk of bias, and six studies had some concerns. CBT is an effective, flexible, and scalable intervention for improving mental health and reducing stigma among PLWH in LMICs.